Film dan propaganda politik (studi atas film “g-30s/pki” dan “jagal”) - Mirnawati Mirnawati (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
This paper examines and compares two films with the theme of political events / history in 1965, namely Pengkhianatan G30S/PKI and Jagal. Both films have the same object but are produced in different time frames. Specifically this paper will parse and analyze how the two films view, tell and visualize events known as the G30S movement. This research is a qualitative descriptive study. Data obtained through observation and film observation and supported by sources from various literature relevant to the theme. The data is analyzed, critically compromised, and then narrated. The film is part of the media used to entertain the audience but the film has other function to spread propaganda. The film Pengkhianatan G30S/PKI, produced by the state in the New Order era, depicts that PKI is an enemy of the state and is trying to overthrow the government. This film is very massive and successfully led to public perception that the events occurred on 30 September 1965 were masterminded by PKI. Meanwhile, Jagal made in the post-reformation period was used to create a new perception that PKI was a victim of the incident. Keywords: Films, Political Propaganda and Public Opinion